Project-Based Learning-STEAM Integrated Web Enhances HOTSEP and Environmental Literacy in Organic And Plastic Waste - Syahmani Syahmani; Rilia Iriani; Leny Leny; Yogo Dwi Prasetyo; Muhammad Noor Raidimas (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2026)
Students need higher-order thinking skills, environmental problems (HOTSEP), and environmental literacy to overcome ecological problems. Alternative solutions using the Project-Based Learning-Science, Technology, Engineering, Art, and Mathematics Learning (PjBL-STEAM) integrated web can enrich students' HOTSEP in the context of wetlands and innovation to overcome environmental problems in daily life and society. The research aims to evaluate the effectiveness of the PjBL-STEAM integrated web approach in improving students' HOTSEP and environmental literacy regarding organic and plastic waste. The research design used is an experimental method with a one-group pretest-post-test design. This study was conducted on 40 chemistry education students at FKIP, Lambung Mangkurat University, Banjarmasin. The data collection technique used a HOTSEP instrument and an environmental literacy questionnaire. Data analysis techniques were used, descriptive analysis with N-gain. The research results show that the PjBL-STEAM integrated web approach can increase students' HOTSEP and environmental literacy competency with an overall gain score > 0.70 in the high category. Student attitudes and behavior show positive actions towards the environment. This research recommends that educational practitioners use the PjBL-STEAM integrated web to develop students' HOTSEP and environmental literacy competencies for education for sustainable environmental development (EESD).